Behaviour of organic compounds in food under high pressure: lipid peroxidation - Kowalski, Elisabeth; Ludwig, Horst; Tauscher, Bernhard (High pressure bioscience and biotechnology, 1996)
We investigated the autoxidation of alpha-linolenic acid under pressure of up to 600 MPa. Three groups of peaks were separated by HPLC and the kinetic…